Pemphigus. Issue 10201 (7th September 2019) - Schmidt, Enno; Kasperkiewicz, Michael; Joly, Pascal
Summary: Pemphigus consists of a group of rare and severe autoimmune blistering diseases mediated by pathogenic autoantibodies mainly directed against two desmosomal adhesion proteins, desmoglein (Dsg)1 and Dsg3 (also known as DG1 and DG3), which are present in the skin and surface-close mucosae. The binding of autoantibodies to Dsg proteins induces a separation of neighbouring keratinocytes, in a process known as acantholysis. The two main pemphigus variants are pemphigus vulgaris, which often originates with painful oral erosions, and pemphigus foliaceus, which is characterised by exclusive skin lesions. Pemphigus is diagnosed on the basis of either IgG or complement component 3 deposits (or both) at the keratinocyte cell membrane, detected by direct immunofluorescence microscopy of a perilesional biopsy, with serum anti-Dsg1 or anti-Dsg3 antibodies (or both) detected by ELISA. Corticosteroids are the therapeutic mainstay, which have recently been complemented by the anti-CD20 antibody rituximab in moderate and severe disease. Rituximab induces complete remission off therapy in 90% of patients, despite rapid tapering of corticosteroids, thus allowing for a major corticosteroid-sparing effect and a halved number of adverse events related to corticosteroids.